Energy and Economic Analysis of a Residential Solar Organic Rankine Plant. (December 2015) - Bocci, E.; Villarini, M.; Vecchione, L.; Sbordone, D.; Di Carlo, A.; Dell'Era, A.
Abstract: To answer the actual energy, water, economic, social and environmental challenges, renewable, distributed power plants need to be developed. Among renewables, solar tri-generative power plants can be a solution where there is big low temperature heating/cooling demand and small electricity demand, like many residential and industrial utilities. In this case, solar thermal plants can produce thermal energy with low cost and high efficiency. The higher temperature heat not needed by the user can be exploited via Organic Rankine Cycle to produce electrical energy and desalinized water via reverse osmosis. The present paper analyses, via TRNSYS simulation, a system composed of 50 m 2 of CPC solar thermal collectors, 3 m 3 of thermal storage, a synthetic heat transfer fluid, 3 kWe ORC, 8 kWth absorber, 200 l/h direct reverse osmosis desalination device. The system is able to produce power, heating/cooling and fresh water needs for a residential house. Although system's components are well known technologies, the integration to a efficient and economic working system is still a challenge. Global energy and economic analyses have been performed. Low temperature heating/cooling terminals allow to increase not only the use of thermal energy but also the ORCand absorber efficiency. ORC-Absorber configuration and relative fluids and temperatures are central. Government support and/or cost reduction of 30% are necessary to have positive NPV and acceptable PBT and IRR.